Search for heavy resonances decaying into two Higgs bosons or into a Higgs boson and a W or Z boson in proton-proton collisions at 13 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Eroe, J.; Del Valle, A. Escalante; Flechl, M.; et al. (Springer Science and Business Media LLC, 2019)
Abstract A search is presented for massive narrow resonances decaying either into two Higgs bosons, or into a Higgs boson and a W or Z boson. The decay channels considered are $$ \mathrm{H}\mathrm{H}\to \mathrm{b}\overline{\mathrm{b}}{\tau}^{+}{\tau}^{-} $$ H H → b b ¯ τ + τ − and $$ \mathrm{V}\mathrm{H}\to \mathrm{q}\overline{\mathrm{q}}{\tau}^{+}{\tau}^{-} $$ V H → q q ¯ τ + τ − , where H denotes the Higgs boson, and V denotes the W or Z boson. This analysis is based on a data sample of proton-proton collisions collected at a center-of-mass energy of 13 TeV by the CMS Collaboration, corresponding to an integrated luminosity of 35.9 fb−1. For the TeV-scale mass resonances considered, substructure techniques provide ways to differentiate among the hadronization products from vector boson decays to quarks, Higgs boson decays to bottom quarks, and quark- or gluon-induced jets. Reconstruction techniques are used that have been specifically optimized to select events in which the tau lepton pair is highly boosted. The observed data are consistent with standard model expectations and upper limits are set at 95% confidence level on the product of cross section and branching fraction for resonance masses between 0.9 and 4.0 TeV. Exclusion limits are set in the context of bulk radion and graviton models:spin-0 radion resonances are excluded below a mass of 2.7 TeV at 95% confidence level. In the spin-1 heavy vector triplet framework, mass-degenerate W′ and Z′ resonances with dominant couplings to the standard model gauge bosons are excluded below a mass of 2.8 TeV at 95% confidence level. These are the first limits for massive resonances at the TeV scale with these decay channels at $$ \sqrt{s}=13 $$ s = 13 TeV.
Keywords: Stabilization; GeV-cms; gravitation: model; triplet; QC770-798; Physics, Particles & Fields; Z'; Hadron-Hadron scattering (experiments); Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics; Nuclear and High Energy Physics; CMS; LHC; Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics; info:eu-repo/classification/ddc/530; model: graviton; gauge boson; Physics; ROOT-S=13 TEV; ddc:530; Higgs physics; higgs physics; channel cross section: branching ratio: upper limit; CERN LHC Coll; Physical Sciences; Physique des particules élémentaires; Particle physics; spin: 1; Higgs particle: pair production; W: associated production; physics; p p: scattering; beyond standard model; hadron-hadron scattering (experiments); higgs physics; Higgs Physics; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; Particles & Fields; spin: 0; Physics Institute; quark; Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics; Beyond Standard Model, Hadron-Hadron scattering (experiments), Higgs physics, Nuclear and High Energy Physics.; Nuclear and High Energy Physics; Mathematical Sciences; experimental particle physics; Science & Technology; Pp collisions; Particle physics; Large hadron collider; CMS; Aerospace Engineering(Formerly Aeronautical Engineering); Large hadron collider; Z0: associated production; Beyond Standard Model; p p: colliding beams; hadronization; Higgs; spin: resonance; FINAL-STATE; vector boson: hadronic decay; Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics; Nuclear and High Energy Physics; Higgs particle: decay; scale: TeV; standard model; high energy physics; High Energy Physics - Experiment; resonance: heavy; High Energy Physics - Experiment (hep-ex); Hadron-Hadron scattering (experiments); [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; hadron-Hadron scattering (experiments); resonance: mass; info:eu-repo/classification/ddc/610; Physical Sciences; tau: pair production; CMS; Nuclear & Particles Physics; Hadron-Hadron Scattering (Experiments); gauge boson: coupling; LHC; branching ratio; narrow resonance; Higg; Physics; Higgs boson; FOS: Physical sciences; bottom: pair production; MASS; Physics; Nuclear and particle physics. Atomic energy. Radioactivity; Higgs particle: leptonic decay